Besser einkaufen durch Social Media? Der Einfluss von Social Plugins auf die Qualität von Produktempfehlungen in E-Commerce-Systemen - Katja Wiedenmann; Florian Botzenhardt; Hans-Michael Ferdinand (Markenbrand, 2015)
– Recommendation systems are a key functionality in e-commerce environments and play a significant role in improving customer loyalty. The quality of the given recommendations is being influenced especially by the amount and the quality of the personal information about the individual customer that can be processed by the software. Internet users tend to provide this information in social networks like Facebook. This article examines the possibilities that arise if e-commerce systems are connected to Facebook. Software like the Facebook Login allow third-party websites to access personal data that users have shared on Facebook. It is very likely that the usage of Facebook plugins can have a positive influence on recommendation systems in e-commerce environments and may help to improve customer satisfaction and loyalty.
Keywords: 650